Lp(a) (Lipoprotein(a)) Levels Predict Progression of Carotid Atherosclerosis in Subjects With Atherosclerotic Cardiovascular Disease on Intensive Lipid Therapy: An Analysis of the AIM-HIGH (Atherothrombosis Intervention in Metabolic Syndrome With Low HDL/High Triglycerides. Issue 3 (March 2018) - Hippe, Daniel S.; Phan, Binh An P.; Sun, Jie; Isquith, Daniel A.; O'Brien, Kevin D.; Crouse, John R.; Anderson, Todd; Huston, John; Marcovina, Santica M.; Hatsukami, Thomas S.; Yuan, Chun; Zhao, Xue-Qiao
Abstract : Objective—: To assess whether Lp(a) (lipoprotein(a)) levels and other lipid levels were predictive of progression of atherosclerosis burden as assessed by carotid magnetic resonance imaging in subjects who have been treated with LDL-C (low-density lipoprotein cholesterol)–lowering therapy and participated in the AIM-HIGH trial (Atherothrombosis Intervention in Metabolic Syndrome With Low HDL/High Triglycerides: Impact on Global Health Outcomes). Approach and Results—: AIM-HIGH was a randomized, double-blind study of subjects with established vascular disease, elevated triglycerides, and low HDL-C (high-density lipoprotein cholesterol). One hundred fifty-two AIM-HIGH subjects underwent both baseline and 2-year follow-up carotid artery magnetic resonance imaging. Plaque burden was measured by the percent wall volume (%WV) of the carotid artery. Associations between annualized change in %WV with baseline and on-study (1 year) lipid variables were evaluated using multivariate linear regression and the Bonferroni correction to account for multiple comparisons. Average %WV at baseline was 41.6±6.8% and annualized change in %WV over 2 years ranged from −3.2% to 3.7% per year (mean: 0.2±1.1% per year; P =0.032). Increases in %WV were significantly associated with higher baseline Lp(a) (β=0.34 per 1-SD increase of Lp(a); 95% confidence interval, 0.15–0.52; P <0.001) after adjusting for clinical risk factors and other lipid levels. On-study Lp(a) had a similar positive association with %WV progression (β=0.33; 95% confidence interval, 0.15–0.52; P <0.001). Conclusions—: Despite intensive lipid therapy, aimed at aggressively lowering LDL-C to <70 mg/dL, carotid atherosclerosis continued to progress as assessed by carotid magnetic resonance imaging and that elevated Lp(a) levels were independent predictors of increases in atherosclerosis burden. Abstract : Supplemental Digital Content is available in the text.